Validity of core needle biopsy in diagnosing primary thyroid lymphoma: a systematic-review and meta-analysis - Nadira Prajnasari Sanjaya; Kevin Varian Marcevianto; Indira Saraswati Sanjaya; Kelvin Kohar; Hayatun Nufus (Universa Medicina, 2026)
BackgroundPrimary thyroid lymphoma (PTL) is a rare thyroid malignancy, accounting for less than 5% of thyroid malignancies. The prognosis of PTL depends on the histologic subtype and stage of disease at diagnosis, hence an effective diagnostic method is needed to ensure prompt treatments. Fine needle aspiration (FNA) is the first test for microscopic examination of a rapidly enlarging thyroid mass, but its limitations and low sensitivity have been observed.  After the often “inconclusive” result is known, core-needle biopsy (CNB) should be performed as the natural next diagnostic step. This systematic review and meta-analysis aimed to evaluate the diagnostic value of core needle biopsy (CNB) in diagnosing PTL. MethodsThis systematic review and meta-analysis follows the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. A PubMed and Embase database search was performed in August 2025. Populations included were patients with final diagnosis of PTL. Pooled sensitivity was calculated using a random-effects model. ResultsThis systematic review and meta-analysis of 12 studies comprised a total of 1091 patients. Core needle biopsy proved to be highly effective, with a pooled sensitivity of 91.6% (95% CI: 82.1%–96.3%). The development of tumor-cell seeding following CNB has been a major concern, but this complication is extremely rare. Other potential complications include bleeding and infection. ConclusionCore needle biopsy demonstrates high diagnostic sensitivity and a favorable safety profile in diagnosing primary thyroid lymphoma, supporting its role as a valuable diagnostic modality, particularly when PTL is clinically suspected or FNA results are inconclusive.